2023
DOI: 10.1101/2023.12.30.573655
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The packaging signal ofXanthomonasintegrative filamentous phages

Ting-Yu Yeh,
Patrick J. Feehley,
Michael C. Feehley
et al.

Abstract: Unlike Ff, the packaging signal (PS) and the mechanism of integrative filamentous phage assembly remain largely unknown. Here we revived twoInoviridaeprophage sequences, φLf2 and φLf-UK, as infectious virions lysogenize black rot pathogenXanthomonas campestrispv.campestris. φLf2 and φLf-UK genomes consist of 6,363 and 6,062 nucleotides and share 85.8% and 98.7% identity with φLf, respectively. To explore their assembly, we first identified 20-26-nucleotide long PS sequences of 10Xanthomonasphages. These PS con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 57 publications
1
7
0
Order By: Relevance
“…Thus far, genomic information has shown that integrative filamentous phages of Gram-negative bacteria lack an Ff gIV and gIX homologue. We also verified that Ff gVII homologues are not present in many integrative filamentous phages (Yeh et al, 2023). The absence of these crucial structures prompted us to identify the PS of these phages, what viral (structural and non-structural) factors are involved in their assembly and egress, and how the PS DNA becomes targeted to the IM for encapsidation.…”
Section: Introductionsupporting
confidence: 65%
See 4 more Smart Citations
“…Thus far, genomic information has shown that integrative filamentous phages of Gram-negative bacteria lack an Ff gIV and gIX homologue. We also verified that Ff gVII homologues are not present in many integrative filamentous phages (Yeh et al, 2023). The absence of these crucial structures prompted us to identify the PS of these phages, what viral (structural and non-structural) factors are involved in their assembly and egress, and how the PS DNA becomes targeted to the IM for encapsidation.…”
Section: Introductionsupporting
confidence: 65%
“…To identify protein factor(s) involved in assembly, we first modified Russel and Model’s method of suppressor screening for PS-interacting protein(s) based on phage plaque morphology (Supplemental Figure S1) (Russel and Model, 1989). We generated a ϕLf-UK phage synonymous T340A/C341G mutant that lost its PS activity but kept gII protein function to facilitate phage DNA replication (Figure 1A and 1C) (Yeh et al, 2023). The ϕLf-UK T340A/C341G plaque morphology was tiny (0.1-0.2 mm) compared to the wild-type phage (1-1.2 mm).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations